Dog soldiers - Stone, Robert 1937-2015 (The Library of America, 2020)
"This volume brings together three novels by one of the most spellbinding writers of his generation, suspenseful masterworks that brilliantly capture the desperate underside of American life in the 1970s and 80s." -- $c Provided by publisher
Keywords: Marginality, Social / United States / Fiction; Nineteen seventies / Fiction; Nineteen eighties / Fiction; Stone, Robert / 1937-2015 / Criticism and interpretation; Stone, Robert / 1937-2015; Marginality, Social; Nineteen eighties; Nineteen seventies; United States; Criticism, interpretation, etc; Fiction; Novels; Fiktionale Darstellung